2011
DOI: 10.1371/journal.pone.0027586
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR4 by Acidosis Increases Endothelial Cell Adhesion through the cAMP/Epac Pathway

Abstract: Endothelium-leukocyte interaction is critical for inflammatory responses. Whereas the tissue microenvironments are often acidic at inflammatory sites, the mechanisms by which cells respond to acidosis are not well understood. Using molecular, cellular and biochemical approaches, we demonstrate that activation of GPR4, a proton-sensing G protein-coupled receptor, by isocapnic acidosis increases the adhesiveness of human umbilical vein endothelial cells (HUVECs) that express GPR4 endogenously. Acidosis in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
168
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(193 citation statements)
references
References 77 publications
18
168
0
Order By: Relevance
“…32 Moreover, human umbilical vein endothelial cells, when treated with acidic pH, increased GPR4-mediated endothelial adhesion to leukocytes. 32,33 Altogether, GPR65 and GPR4 provide differential regulation of the inflammatory response through their acid sensing capabilities. GPR65 predominately demonstrates function in the inhibition of the inflammatory response whereas GPR4 activation exacerbates inflammation.…”
Section: Gpr65 (Tdag8)mentioning
confidence: 99%
See 3 more Smart Citations
“…32 Moreover, human umbilical vein endothelial cells, when treated with acidic pH, increased GPR4-mediated endothelial adhesion to leukocytes. 32,33 Altogether, GPR65 and GPR4 provide differential regulation of the inflammatory response through their acid sensing capabilities. GPR65 predominately demonstrates function in the inhibition of the inflammatory response whereas GPR4 activation exacerbates inflammation.…”
Section: Gpr65 (Tdag8)mentioning
confidence: 99%
“…The GPR4 receptor is highly expressed in vascular endothelial cells. 33,44 GPR4 is activated by extracellular acidic pH to initiate signaling cascades which regulate cellular function. 19,33,45,46 It has been reported that GPR4 is a functional pH sensor in vascular …”
Section: Role For the Ph-sensing Gpcrs In The Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, TDAG8 has been shown to mediate acidic pH-induced inhibition of apoptosis in eosinophils [50], inflammatory cytokine production in macrophages [51], and O 2 -production in neutrophils [52]. As for GPR4, this receptor subtype has been reported to mediate acidic-pH-induced stimulation of monocyte adhesion in association with the expression of VCAM-1 [53] and a number of inflammatory genes [54]. In these previous studies, protonsensing GPCRs mediate responses to acidic environments of less than pH 7.0, which may be attained under inflammatory lesions [39].…”
Section: In Vitro Analysis Of Insulin Secretionmentioning
confidence: 98%